Lixiviação férrica, química e bacteriana de sulfetos secundários de cobre - Erick Adan Rivera Rojas (2009)
In the present work, the chemical and bacterial leaching of a secondary copper sulphide (Calcocite (Cu2S) and Covellite (CuS)) from low grade copper ores had been studied. In the chemical leaching, the effect of several parameters on the kinetics of the copper extraction had been evaluated, as initial Fe3+ concentration in the leaching solution (1 to20g.L-1), temperature (30 to 80"C), initial sulphuric acid concentration (0.1 to lmol.L-1), solid percentage in the reactor (l to 10% w/v) and ore fraction size (- 52 to l48um). Two leaching stages had been observed: the first is represented by a fast copper extraction due to the rapid leaching of Calcocit , reaching more than 50% of the metal extraction in the first 5 minutes; the second, which is slower than the fonner, corresponds to the leaching of Covellite, for which a mix kinetic is suggested, with the chemical reaction at the sulphide surface as the controlling step of the process (Ea Z 51,79kJ .mol-1). The copper extraction revealed a strong dependence on temperature and an independence on initial Fe3+ concentration (above 4g.L-1), on the ore fraction sizes and on the sulphuric acid concentration (above 0.25rnol.L-1). 98% of copper extraction had been reached by chemical leaching, carried through a temperature of 80"C. For the bioleaching study, a bacteria culture of Acidithiobacillus was used (Aciclithiobacillus ferrooxidans) and the parameters evaluated was the initial Fe2+ concentration in the culture (l to l0g.L-1), the solid percentage in the reactor (1 to 10% w/v) and the ore size fraction (-52 to 148um). The results suggest an indirect mechanism with respect to the process of copper extraction, where the bacteria oxidize the Fe2+ to Fe3+ which consists in an oxidant agent that becomes possible the leaching of the interest metal. The copper extraction revealed independent on the ore size fraction and the Fe2+ initial concentrations (above 2g.L-1). It was also observed a decrease in thecopper extraction rate with an increase of the amount of solids added into the reactor. The copper extraction percentage was, approximately, 90% for the bioleaching, carried through with an equal solid percentage (1.0% m/v).